Urinary Angiotensinogen-Melatonin Ratio in Gestational Diabetes and Preeclampsia - Valias, Gabriela Ribeiro; Gomes, Patricia Rodrigues Lourenço; Amaral, Fernanda G.; Alnuaimi, Saif; Monteiro, Daniela; O'Sullivan, Siobhán; Zangaro, Renato; Cipolla-Neto, José; Acuna, Juan; Baltatu, Ovidiu Constantin; Campos, Luciana Aparecida (Frontiers in Molecular Biosciences, 2022)
Background: A large research portfolio indicates that an activated renal renin-angiotensin system or a deficit on melatonin is associated with several cardiovascular pathologies. In this observational clinical study, we hypothesized that alterations in urinary melatonin or angiotensinogen levels may be altered in two common conditions, preeclampsia and gestational diabetes. Our study’s primary objective was to assess melatonin and angiotensinogen as novel disease biomarkers detectable and quantifiable in the urine of pregnant women with or without pregnancy complications. Methods: This was a concurrent cohort study of pregnant women with selected obstetric pathologies (gestational diabetes, preeclampsia, hypertension and obesity with hypertension). A group of healthy controls was also included. Urinary 6-sulfatoxymelatonin and angiotensinogen were measured by sensitive and specific ELISAs in first morning void urine samples. The patients were included in the cohort consecutively, and the diagnosis was blinded at the level of urine collection. Urinary 6-sulfatoxymelatonin and angiotensinogen levels were investigated in the patients included in the cohort. Results: Urinary levels of angiotensinogen were significantly higher in the gestational diabetes [angiotensinogen/creatinine ratio median (25th, 75th): 0.11 (0.07, 0.18)] and preeclampsia [0.08 (0.06, 0.18)] groups than in those with healthy pregnancy [0.05(0.04, 0.06]; 6-sulfatoxymelatonin levels were significantly lower in the gestational diabetes [ug/h: median (25th, 75th): 0.12(0.08, 0.17)] and preeclampsia [0.12 (0.09, 0.15)] groups than in those with healthy pregnancy [0.20 (0.15, 0.27]. Neither morning void protein/creatinine ratio nor 24-h urine protein estimate were significantly different between the study groups. Conclusion: These results suggest that urinary angiotensinogen levels may indicate an intrarenal RAS activation while melatonin production appears to be defective in gestational diabetes or hypertension. An angiotensinogen/melatonin ratio is suggested as an early biomarker for identification of gestational diabetes or hypertension. This report provides a basis for the potential use of melatonin for the treatment of preeclampsia. A prospective study in a larger number of patients to determine the operative characteristics of these markers as potential diagnostic tests is justified.